Activin A targets extrasynaptic NMDA receptors to ameliorate neuronal and behavioral deficits in a mouse model of Huntington disease - Nassrallah, Wissam B.; Ramandi, Daniel; Cheng, Judy; Oh, Jean; Mackay, James; Sepers, Marja D.; Lau, David; Bading, Hilmar; Raymond, Lynn A. (Neurobiology of disease, 2023)
Cortical-striatal synaptic dysfunction, including enhanced toxic signaling by extrasynaptic N-methyl-d-aspartate receptors (eNMDARs), precedes neurodegeneration in Huntington disease (HD). A previous study showed Activin A, whose transcription is upregulated by calcium influx via synaptic NMDARs, suppresses eNMDAR signaling. Therefore, we examined the role of Activin A in the YAC128 HD mouse model, comparing it to wild-type controls. We found decreased Activin A secretion in YAC128 cortical-striatal co-cultures, while Activin A overexpression in this model rescued altered eNMDAR expression. Striatal overexpression of Activin A in vivo improved motor learning on the rotarod task, and normalized striatal neuronal eNMDAR-mediated currents, membrane capacitance and spontaneous excitatory postsynaptic current frequency in the YAC128 mice. These results support the therapeutic potential of Activin A signaling and targeting eNMDARs to restore striatal neuronal health and ameliorate behavioral deficits in HD.
Gesehen am 14.05.2024